"Stan panów"? Miejsce "Herrenstandu" w systemie prawnym, administracyjnym i ustrojowym Śląska w epoce habsburskiej (1526-1740) = "The Lords State of the Realm"? German "Herrenstand" in the Public and Administrative System of Silesia in the Habsburgian Era 1526-1740 - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The term "Lords state of the realm", German "Herrenstand", in the modern Polish history is actually unclear. In connection with the medieval origins of the concept, Polish historiography formulate them somewhat linear. The, so called, second state of the realm, nobility, originating from military orientated chivalry had many major privileges concerning their political and economic functions in the aristocratic, cosmopolitan society. The Lords state oft he realm stemed from the German word "Herrenstand". It was a group of dukes, earls, counts and barons.
Keywords: Herrenstand; stan panów; arystokracja; Śląsk; hrabiowie; baranowie; the lords state; Aristocracy; Silesia; counts; barons